2017
DOI: 10.1099/jgv.0.000797
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol 25-hydroxylase acts as a host restriction factor on pseudorabies virus replication

Abstract: Cholesterol 25-hydroxylase (CH25H) catalyses the production of 25-hydroxycholesterol (25HC) from cholesterol by adding a second hydroxyl group at position 25. The aim of this study was to examine the antiviral effect of CH25H on pseudorabies virus (PRV), a swine pathogen that can cause devastating disease and economic losses worldwide. The results showed that porcine ch25h was induced by either interferon or PRV infection. PRV infection of porcine alveolar macrophages (3D4/21 cells) was attenuated by CH25H ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…In each cell, 500 to 1,000 ISGs are induced and subsequently block multiple stages of the viral life cycle [55,56]. Our previous study has demonstrated that porcine cholesterol 25-hydroxylase (CH25H) is regulated by IFNs, and 25-hydroxycholesterol (25HC) inhibits PRV entry [57]. CH25H expression is also induced in response to infection with Zika virus, Singapore grouper iridovirus and red-spotted grouper nervous necrosis virus, and subsequently blocks viral attachment by 25HC [58,59].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…In each cell, 500 to 1,000 ISGs are induced and subsequently block multiple stages of the viral life cycle [55,56]. Our previous study has demonstrated that porcine cholesterol 25-hydroxylase (CH25H) is regulated by IFNs, and 25-hydroxycholesterol (25HC) inhibits PRV entry [57]. CH25H expression is also induced in response to infection with Zika virus, Singapore grouper iridovirus and red-spotted grouper nervous necrosis virus, and subsequently blocks viral attachment by 25HC [58,59].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…PRV-GFP, PRV-QXX and PRRSV-BJ4 were used as previously described [57,72,74]. VSV-GFP, NDV-GFP and H1N1-PR8 were gifts from Yong-Tao Li (Henan Agricultural University, China) [75].…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Upon activation by the innate immune pathways, IFNs bind to cell surface receptors and initiate a signaling cascade through the Janus kinase signal transducer and activator of transcription (JAK-STAT) pathway, leading to the transcriptional regulation of hundreds of IFN-stimulated genes (ISGs) that are highly effective at resisting and controlling pathogens [10,11]. We previously found that porcine cholesterol 25-hydroxylase (CH25H) is an ISG induced by either IFN or PRV infection [12]. CH25H catalyzes 25hydroxycholesterol production to inhibit PRV entry.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have illustrated that CH25H can be upregulated by some viruses, including HCV, PRRSV, and PRV (Anggakusuma et al, 2015;Song et al, 2017;Wang et al, 2017). In the present study, we investigated whether PEDV infection could upregulate CH25H expression in Vero cells.…”
Section: Pedv Infection Downregulates Ch25h Expression and Ch25h Is mentioning
confidence: 90%
“…At present, many anti-PEDV therapies are in general use, including recombinant Lactobacillus casei expressing dendritic cell-targeting peptide fused with the COE protein of PEDV (Langel et al, 2016), and IFNlambda, which preferably inhibits PEDV infection (Li et al, 2017b). Previous studies revealed that CH25H can be induced by several viruses, including HCV, PRRSV, and PRV (Anggakusuma et al, 2015;Song et al, 2017;Wang et al, 2017). In contrast, the present study demonstrates that CH25H expression can be downregulated by PEDV infection, and CH25H cannot be induced by IFN-α in Vero cells.…”
Section: Discussionmentioning
confidence: 99%